DEVELOPMENT AND VALIDATION OF A METHOD FOR DETECTING THE BRAF V600E SOMATIC MUTATION BY THE ALLELE-SPECIFIC LAMP METHOD - Filipenko, M.L.; Khrapov , E.A.; Shamovskaya , D.V.; Smertina , M.A.; Obrabin , I.P.; Boyarskikh , U.A. (Eurasian Journal of Applied Biotechnology, 2026)
Detection of the somatic BRAF V600E mutation is a mandatory component of molecular stratification in melanoma, as its presence determines eligibility for BRAF and MEK inhibitor therapy [1–4]. Although qPCR- and NGS-based platforms remain the most widely used approaches for BRAF V600 mutation testing, interest in simpler, faster, and more cost-effective isothermal amplification formats persists [7, 22]. To develop and validate an allele-specific loop-mediated isothermal amplification (LAMP) assay for detection of the somatic BRAF V600E mutation in DNA extracted from tumour tissue. An allele-specific LAMP format was employed. Analytical performance was characterised using linearised plasmid controls pV600WT and pV600E and their mixtures. Diagnostic validation was performed on 67 DNA samples extracted from FFPE melanoma blocks. The cobas 4800 BRAF V600 Mutation Test was used as the reference method. The analytical limit of detection for mutant allele fraction was 1%, and the LoD₅₉ for mutant allele copy number was 200 copies per reaction. In the clinical sample set, sensitivity of LAMP-V600E relative to AS-qPCR was 93.5% (29/31), specificity 100% (36/36), positive predictive value 100%, negative predictive value 94.7%, overall accuracy 97.0%, and Cohen’s kappa coefficient 0.940. The two false-negative results were most likely attributable to FFPE-DNA degradation and the greater sensitivity of LAMP to template integrity over the comparatively longer amplification target [23, 24]. The developed allele-specific LAMP assay for BRAF V600E detection demonstrates high specificity, acceptable clinical sensitivity, and strong concordance with the reference AS-qPCR platform. The assay may be considered a rapid and technically accessible option for tissue-based BRAF testing; however, the quality and quantity of FFPE-derived DNA must be taken into account for reliable performance.